Low-entropy high-nickel positive electrode material, lithium ion battery and preparation method

By doping polyvalent metal elements into the positive electrode material of lithium-ion batteries, adjusting the configuration entropy to form lithium-rich oxides, the problem that lithium-ion batteries are difficult to reduce safety risks while increasing the energy density, and excellent electricity is achieved Chemical activity and safety performance.

CN119400850APending Publication Date: 2025-02-07XTC NEW ENERGY MATERIALS(XIAMEN) LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411452294.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

While increasing the energy density of existing lithium-ion battery materials, it is difficult to effectively reduce safety risks and hidden dangers. Especially after the nickel content increases, the thermal runaway temperature of the battery drops, resulting in a decrease in safety performance.

Method used

Using low-entropy high-nickel positive electrode material, the configuration entropy of the material is adjusted to form Li-X-O lithium-rich oxides and optimize the crystals of the material by doping metal elements with polyvalent states such as Ti, Zr, Ta, Nb and W. Grid structure and interface characteristics.

Benefits of technology

Through the modification of configuration entropy, oxygen loss in the nickel redox center is suppressed, grain arrangement is optimized, reactive oxygen release is reduced, electrochemical activity and safety performance is improved, while maintaining high specific capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400850A_ABST
    Figure CN119400850A_ABST
Patent Text Reader

Abstract

The invention provides a low-entropy high-nickel positive electrode material, a lithium ion battery and a preparation method. The low-entropy high-nickel positive electrode material is doped with one or more metal elements with multiple valence states, and the configuration entropy modification value of the low-entropy high-nickel positive electrode material is delta Sconfigure; 0.2 R, the chemical general formula is LiNi Co Mn < c > X (1-a-b-c) O < 2 >, and X is a metal cation. According to the invention, through the configuration entropy of the multi-valence metal element doped modified material, the performance of the positive electrode material has the ultrahigh specific capacity and good cycle performance of an unmodified material, and the configuration entropy modification range (delta Sconult; 0.2 R), the oxygen release of lattice oxygen is inhibited, and the structural stability of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a low-entropy high-nickel positive electrode material, a lithium-ion battery and a preparation method thereof. Background Art

[0002] With the development of lithium battery applications in various fields, safety issues of lithium batteries have frequently occurred. How to reduce safety risks and hidden dangers while increasing the energy density of lithium batteries has become an important direction for battery research and development. High specific energy batteries are still mainly based on ternary materials. With the increase of nickel content, the energy density of the battery is further improved, but it is also accompanied by a decrease in the thermal runaway temperature of the lithium battery. Therefore, the development of ternary lithium batteries with high specific capacity and high safety performance is an important upgrade direction for future products.

[0003] Existing lithium-ion battery materials include ternary materials, lithium iron phosphate materials, lithium cobalt oxide materials, lithium manganese oxide materials, etc. Among them, ternary materials have the advantages of high discharge capacity, good cycle performance, and low price, and occupy an important position in the field of electric vehicles and large-scale energy storage. Element doping is a relatively effective strategy to improve the performance of ternary materials. However, different types of doping elements and different orders of magnitude of doping element amounts often result in different doping effects, and sometimes even cause a decrease in the performance of a certain aspect of the positive electrode material. How to effectively achieve doping modification of the positive electrode material has become a technical difficulty.

[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present invention, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a low-entropy high-nickel positive electrode material, a lithium-ion battery and a preparation method.

[0006] According to a first aspect of the present invention, a low-entropy high-nickel cathode material is provided, wherein the low-entropy high-nickel cathode material is doped with one or more metal elements having a multivalent state, and the configuration entropy modification value ΔS of the low-entropy high-nickel cathode material is config <0.2R.

[0007] In an exemplary embodiment of the present invention, the chemical formula of the low entropy high nickel cathode material is LiNi a Co b Mn c X (1-a-b-c) O2, wherein X is a metal cation selected from Ti +4 、Ti +2 、Zr +4 、Zr +2 ,Ge +4 ,Ge+2 Sn +4 Sn +2 、 +5 、 +4 、 +3 , Nb +5 , Nb +4 , Nb +3 、As +5 、As +3 , Sb +5 , Sb +3 、V +5 、V +4 、Ru +5 、Ru +4 、Se +6 、Se +4 , W +6 , W +4 、Mo +6 and Mo +4 One or more of the following; 0.8≤a<1, 0.01≤b<0.1, 0.01≤c<0.1.

[0008] In an exemplary embodiment of the present invention, the configuration entropy S of the low entropy high nickel positive electrode material is config satisfy: Among them, x i is the mole fraction of the cation and x j is the molar fraction of anions, N is the number of corresponding cation / anion elements; R is the universal gas constant, R = 8.314 J.mol -1 ·K -1 ,S config <1R is a low entropy cathode material; configuration entropy modification value ΔS config is the difference in configuration entropy before and after modification of the cathode material.

[0009] In an exemplary embodiment of the present invention, part of the metal elements forms Li-XO lithium-rich oxide at the interface or near the surface of the low-entropy high-nickel positive electrode material.

[0010] In an exemplary embodiment of the present invention, X is preferably Ti +4 、Ti +2 、Zr +4 、Zr +2 、 +5 、 +4 、 +3 , Nb +5 , Nb +4 , Nb +3 , W +6 and W +4 One or more of .

[0011] In an exemplary embodiment of the present invention, the low-entropy high-nickel positive electrode material is doped with no more than three metal elements.

[0012] In an exemplary embodiment of the present invention, the metal cation matches the lattice of the low entropy high nickel positive electrode material, and the radius of the metal cation is And / or, the grain size of the low-entropy high-nickel positive electrode material is 80 to 110 nm; and / or, the crystal parameter c-axis of the low-entropy high-nickel positive electrode material is higher than 14.19.

[0013] According to a second aspect of the present invention, there is provided a method for preparing a low-entropy high-nickel positive electrode material as described in any one of the above, comprising:

[0014] S1, ball milling a high-nickel ternary precursor, a lithium source, and a metal source to obtain a mixture; wherein the metal element X of the metal source has multiple valence states;

[0015] S2, placing the mixture in an oxygen environment, heating it to 500-600° C., calcining it for 1-6 hours, then heating it to 650-850° C., calcining it for 10-15 hours, and cooling it to room temperature to obtain a first product;

[0016] S3, washing, separating and drying the first product by using a salt-free water solution to obtain a second product;

[0017] S4, placing the second product in an oxygen atmosphere, heating it to 200-400° C., performing secondary calcination, and cooling it to room temperature after calcination to obtain the low-entropy high-nickel positive electrode material.

[0018] In an exemplary embodiment of the present invention, the lithium source is selected from one or more of lithium hydroxide, lithium fluoride and lithium carbonate; the metal source is selected from one or more of oxides, fluorides, carbonates, phosphates and oxalates containing element X, and the metal source is further preferably one or more of ZrO2, TiO2, Nb2O5, TaO2 and WO3.

[0019] In an exemplary embodiment of the present invention, in step S1, the molar ratio of the metal ions in the high-nickel ternary precursor and the metal source is (90-100):(10-0).

[0020] In an exemplary embodiment of the present invention, in step S2, the heating rate is 5 to 15°C / min; and / or, in step S4, the secondary calcination time is 4 to 10 hours.

[0021] According to a third aspect of the present invention, a lithium-ion battery is provided, comprising a low-entropy, high-nickel cathode material as described in any one of the above items and / or a low-entropy, high-nickel cathode material prepared according to the preparation method as described in any one of the above items.

[0022] The beneficial effects of the low-entropy high-nickel positive electrode material, lithium-ion battery and preparation method of the embodiments of the present invention are:

[0023] The low-entropy high-nickel cathode material provided by the embodiment of the present invention can not only promote the radial arrangement of primary grains to suppress the generation of microcracks, but also induce the growth of particles in the direction of low stress, regulate the oxygen loss of nickel redox centers under high voltage, and interact with Li at the interface or near the surface through the strategy of configuration entropy-assisted doping and modification of high-nickel cathode materials. + , O 2- The reaction forms an ion conductive layer, which inhibits the release of active oxygen without affecting the high specific capacity of the main body of the material. The resulting low-entropy high-nickel positive electrode material has excellent electrochemical activity and safety performance.

[0024] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present disclosure and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 This is a schematic diagram of the doping structure of the high-nickel positive electrode material according to an embodiment of the present invention;

[0027] Figure 2 CP-SEM images of high-nickel positive electrode materials prepared in Comparative Example 1 and Examples 1 to 3 of the present invention;

[0028] Figure 3 CP-SEM-EDS image of the high-nickel positive electrode material prepared in Example 5 of the present invention;

[0029] Figure 4 CP-SEM-EDS image of the high-nickel positive electrode material prepared in Comparative Example 2 of the present invention;

[0030] Figure 5 This is a comparison chart of XRD of the high nickel positive electrode material prepared in Example 4 of the present invention and that of Comparative Example 1;

[0031] Figure 6This is a comparison chart of XRD of the high nickel positive electrode material prepared in Example 5 of the present invention and that of Comparative Example 1;

[0032] Figure 7 This is a comparison chart of XRD of the high nickel positive electrode material prepared in Example 6 of the present invention and that of Comparative Example 1;

[0033] Figure 8 CP-SEM morphology of the high nickel positive electrode material prepared in Comparative Example 1 of the present invention before and after cycling;

[0034] Fig. 9 This is the CP-SEM morphology of the high-nickel positive electrode material prepared in Example 2 of the present invention before and after cycling.

[0035] Fig.10 The battery EIS graphs of the high-nickel positive electrode materials prepared in Comparative Example 1 and Example 2 of the present invention before and after 50 cycles. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical scheme and advantages of the embodiments of the present disclosure clearer, the technical scheme in the embodiments of the present disclosure will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0037] The low-entropy high-nickel positive electrode material, lithium-ion battery and preparation method of the embodiments of the present invention are described in detail below.

[0038] The embodiment of the present invention provides a low-entropy high-nickel cathode material doped with one or more metal elements with multivalent states, and the configuration entropy modification value ΔS of the low-entropy high-nickel cathode material is config <0.2R.

[0039] By doping multivalent metal elements in the positive electrode material, the ionic radius and bond energy of the multivalent metal elements construct the configuration entropy of the positive electrode material. The configuration entropy-assisted doping and modification of the high-nickel positive electrode material can not only promote the radial arrangement of the primary grains to inhibit the generation of microcracks, but also induce the particles to grow in the direction of low stress; regulate the oxygen loss of the nickel redox center under high voltage, and interact with Li at the interface or near the surface. + , O 2 - The reaction forms an ion conductive layer, which inhibits the release of active oxygen without affecting the high specific capacity of the main body of the material, thereby improving the stability of active oxygen in lithium-ion batteries and the energy density of the material.

[0040] Specifically, in this embodiment, the chemical formula of the low entropy high nickel positive electrode material is LiNi a Co bMn c X (1-a-b-c) O2, wherein X is a metal cation selected from Ti +4 、Ti +2 、Zr +4 、Zr +2 ,Ge +4 ,Ge +2 Sn +4 Sn +2 、 +5 、 +4 、 +3 , Nb +5 , Nb +4 , Nb +3 、As +5 、As +3 , Sb +5 , Sb +3 、V +5 、V +4 、Ru +5 、Ru +4 、Se +6 、Se +4 , W +6 , W +4 、Mo +6 and Mo +4 One or more of the following; 0.8≤a<1, 0.01≤b<0.1, 0.01≤c<0.1.

[0041] Specifically, the configuration entropy S of the low-entropy high-nickel cathode material is config satisfy: Among them, x i is the mole fraction of the cation and x j is the molar fraction of anions, and N is the number of corresponding cation / anion elements. i and j start from 1 until i = N / j = N. The number of cations and anions can be the same or different. R is the universal gas constant, R = 8.314 J.mol -1 ·K -1 ,S config <1R is a low entropy cathode material; configuration entropy modification value ΔS config It is the entropy difference before and after the cathode material is modified.

[0042] It should be noted that the configuration entropy modification value ΔS config That is, the difference between the configuration entropy of the high nickel cathode material without metal cations and the configuration entropy of the low entropy high nickel cathode material obtained after doping with metal cations. Except for the doped metal cations, the materials before and after doping remain consistent in other components, dosages and preparation parameters.

[0043] ΔS of the positive electrode material of this embodimentconfig <0.2R, further preferably, ΔS of the positive electrode material config Satisfy: 0.09R≤ΔS config ≤0.12R. By increasing the configuration entropy through element doping, the following technical effects can be obtained: a. Oxygen vacancies are confined to the vicinity of the dopant, reducing the oxygen loss of the Ni redox center; b. Optimizing the radial arrangement of primary grains, inhibiting the generation of microcracks, reducing lattice distortion and structural collapse; c. Utilizing the hysteresis diffusion effect brought about by the entropy increase, forming the difference between neighboring atoms between crystal sites, thereby increasing the migration barrier of the transition diffusion between sites, thereby regulating the internal element distribution of the material, inducing the particles to grow in the direction of low stress, and reducing the microscopic strain (ε) in the crystal structure of the bulk material. S config Affected by the molar fraction of each metal element, the Ni content in high-nickel cathode materials plays a decisive role in the energy density and configurational entropy of the material. config When it exceeds 0.2R, although the safety performance of high-nickel positive electrode materials can be improved to a certain extent, the electrochemical performance of the materials is significantly reduced and is not sufficient to meet the requirements of material development.

[0044] Furthermore, considering the lattice matching problem of metal cations, the metal cation X is preferably Ti +4 、Ti +2 、Zr +4 、Zr +2 、 +5 、 +4 、 +3 , Nb +5 , Nb +4 , Nb +3 , W +6 and W +4 The selection of the above metal cations can form a stronger metal oxygen bond, which can ensure that the material has a more stable structure and phase during high lithium removal, while reducing the generation of oxygen vacancies and thus reducing oxygen loss.

[0045] Furthermore, the low entropy high nickel cathode material is doped with no more than three metal elements. Specifically, the metal cation X is selected from one, two or three of the five elements Ti, Zr, Ta, Nb and W. Too many different elements doping to form a complex metal layer environment can easily lead to structural distortion and Li / Ni mixing. At the same time, the large difference in neighboring atoms between sites increases the transition diffusion barrier between sites.

[0046] For further information, see Figure 1 , some metal elements form Li-XO lithium-rich oxide at the interface or near the surface of the low-entropy high-nickel cathode material.+ , O 2- The reaction forms an ion conductive layer. Li-XO includes but is not limited to Li2TiO3, Li2ZrO3, Li6WO6, Li6MoO6, Li3NbO4, Li3TaO4 and other lithium-rich oxides. Through this structure, the material can capture active oxygen without affecting the main body of the material, and improve the interface layer Li during the charge and discharge process. + Therefore, the metal oxygen bond formed when the cation doping occupies the transition metal position and enters the bulk phase can stabilize the crystal lattice and, for charge balance, inhibit the diffusion to Ni under high voltage. 4+ transformation, thereby inhibiting the oxidation release of lattice oxygen, reducing side reactions under high voltage, and improving structural stability under high voltage.

[0047] Furthermore, the metal cations are lattice-matched with the low-entropy high-nickel cathode material, and the metal cation radius is Further preferably, the metal cation radius is The cations with variable valence will undergo redox reactions during the charge and discharge process of the positive electrode material, thus increasing the energy density of the positive electrode material. and below Cation doping can easily lead to material lattice distortion, structural collapse and Li / Ni mixing. At the same time, the large difference in neighboring atoms between crystal sites will also increase the migration barrier of inter-site transition diffusion. By selecting metal cations that match the lattice, the interlayer spacing can be expanded while changing the lattice parameters, becoming the "support point" of the layered structure, reducing the binding energy of the Li-O bond, and improving the kinetic properties of the material.

[0048] Furthermore, the grain size of the low entropy high nickel cathode material is 80-110 nm; further, the crystal parameter c-axis of the low entropy high nickel cathode material is higher than 14.19. The high nickel cathode material under this range of parameters can show better rate performance.

[0049] This embodiment also provides a method for preparing the low-entropy high-nickel positive electrode material as described above, comprising:

[0050] S1, ball milling a high-nickel ternary precursor, a lithium source, and a metal source to obtain a mixture; wherein the metal element X of the metal source has multiple valence states;

[0051] S2, placing the mixture in an oxygen environment, heating it to 500-600° C., calcining it for 1-6 hours, then heating it to 650-850° C., calcining it for 10-15 hours, and cooling it to room temperature to obtain a first product;

[0052] S3, washing, separating and drying the first product by using a salt-free water solution to obtain a second product;

[0053] S4, placing the second product in an oxygen atmosphere, heating it to 200-400° C., performing secondary calcination, and cooling it to room temperature after calcination to obtain the low-entropy high-nickel positive electrode material.

[0054] Furthermore, in step S1, the lithium source is selected from one or more of lithium hydroxide, lithium fluoride and lithium carbonate; preferably lithium hydroxide.

[0055] Further, in step S1, the metal source is selected from one or more of oxides, fluorides, carbonates, phosphates and oxalates containing element X, preferably oxides containing element X. Further, the metal source is further preferably one or more of ZrO2, TiO2, Nb2O5, TaO2 and WO3.

[0056] Furthermore, in step S1, the molar ratio of the metal ions in the high nickel ternary precursor and the metal source is (90-100):(10-0). Furthermore, the molar ratio of the metal ions in the metal source to the lithium ions in the lithium source is 1:(1.05-1.10). By regulating the amount of metal elements, high nickel ternary precursor and lithium ions, the doping amount is controlled to construct the configuration entropy.

[0057] Furthermore, in step S1, ball milling can be performed in a ball milling jar for 0.5 to 12 hours. Pre-ball milling mixing is helpful to form a good doping effect.

[0058] Further, in step S2, the heating rate to 500-600°C is 5-15°C / min, and / or the heating rate to 650-850°C is 5-15°C / min. In this step, a low-temperature short-time calcination (500-600°C, 1-6h) is first performed, and then a high-temperature long-time calcination (650-850°C, 10-15h) is performed, which can achieve pre-lithiation and aging of the material to obtain an ordered layered structure material.

[0059] Furthermore, in step S4, the secondary calcination time is 4 to 10 hours. By performing the secondary calcination at a lower temperature (200 to 400° C.), the material defects caused by the water washing in step S3 can be passivated, thereby achieving material repair.

[0060] The present invention also provides a lithium-ion battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the low-entropy high-nickel positive electrode material described above. It is understood that the lithium-ion battery can be prepared according to known methods in the prior art.

[0061] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0062] Example 1

[0063] This embodiment provides a low entropy high nickel positive electrode material Li (Ni 0.94 Co 0.04 Mn 0.01 Ti 0.01 )O2, follow the steps below to obtain:

[0064] Step (1) Weigh 2000.0 g of Ni 0.95 Co 0.04 Mn 0.01 (OH)2 high-nickel ternary precursor, 17.3 g of TiO2 and 961.5 g of LiOH were fully mixed in a ball mill to obtain a mixture.

[0065] Step (2) The mixture is placed in an oxygen environment and calcined at 560° C. for 2 h, then heated to 710° C. at a rate of 10° C. / min and calcined for 11 h, cooled to room temperature, and sieved to obtain product 1.

[0066] Step (3) The product 1 is washed with free salt water at low temperature of 15°C for 10 minutes with sufficient stirring to wash away residual lithium and filter and separate. The total time is controlled within 18 minutes. The drying procedure in a vacuum oven is: drying at 60°C for 2 hours + drying at 130°C for 6 hours to obtain product 2.

[0067] Step (4) The product 2 is calcined at 250°C for 6 hours under an oxygen atmosphere, cooled to room temperature, and sieved to obtain the finished product Li(Ni 0.94 Co 0.04 Mn 0.01 Ti 0.01 )O2.

[0068] The high nickel positive electrode material prepared in this example was subjected to an X-ray diffraction (XRD) test, and Topas refinement showed that the grain size was 106.4 nm and the lattice parameter c-axis was 14.1936.

[0069] Example 2

[0070] This embodiment provides a low entropy high nickel positive electrode material Li (Ni 0.93 Co 0.04 Mn 0.01 Ti 0.02 )O2, which is different from Example 1 in that:

[0071] Step (1): Weigh 2000.0 g of Ni 0.95 Co 0.04 Mn 0.01 The (OH)2 high-nickel ternary precursor, 34.6 g of TiO2 and 971.0 g of LiOH were fully mixed in a ball mill to obtain a mixture.

[0072] Step (2) The mixture is placed in an oxygen environment and calcined at 560° C. for 2 h, then heated to 740° C. at a rate of 10° C. / min and calcined for 11 h, cooled to room temperature, and sieved to obtain product 1.

[0073] The high nickel positive electrode material prepared in this example was subjected to an X-ray diffraction (XRD) test, and Topas refinement showed that the grain size was 98.6 nm and the lattice parameter c-axis was 14.2124.

[0074] Example 3

[0075] This embodiment provides a low entropy high nickel positive electrode material Li (Ni 0.93 Co 0.04 Mn 0.01 Ti 0.01 Zr 0.01 )O2, which is different from Example 1 in that:

[0076] Step (1) Weigh 2000.0 g of Ni 0.95 Co 0.04 Mn 0.01 (OH)2 high-nickel ternary precursor, 17.3 g of TiO2, 26.8 g of ZrO2 and 971.1 g of LiOH were fully mixed in a ball mill to obtain a mixture.

[0077] Step (2) The mixture is placed in an oxygen environment and calcined at 560° C. for 2 h, then heated to 740° C. at a rate of 10° C. / min and calcined for 11 h, cooled to room temperature, and sieved to obtain product 1.

[0078] The high nickel positive electrode material prepared in this example was subjected to an X-ray diffraction (XRD) test, and Topas refinement showed that the grain size was 100.4 nm and the lattice parameter c-axis was 14.2118.

[0079] Example 4

[0080] This embodiment provides a low entropy high nickel positive electrode material Li (Ni 0.92 Co 0.04 Mn 0.01 Ti 0.02 Nb 0.01 )O2, which is different from Example 1 in that:

[0081] Step (1) Weigh 2000.0 g of Ni 0.95 Co 0.04 Mn 0.01 (OH)2 high-nickel ternary precursor, 34.6g of TiO2, 29.4g of Nb2O5 and 981.0g of LiOH were fully mixed in a ball mill to obtain a mixture.

[0082] Step (2) The mixture is placed in an oxygen environment and calcined at 560° C. for 2 h, then heated to 760° C. at a rate of 10° C. / min and calcined for 11 h, cooled to room temperature, and sieved to obtain product 1.

[0083] The high nickel positive electrode material prepared in this example was subjected to an X-ray diffraction (XRD) test, and Topas refinement showed that the grain size was 104.8 nm and the lattice parameter c-axis was 14.2220.

[0084] Example 5

[0085] This embodiment provides a low entropy high nickel positive electrode material Li (Ni 0.92 Co 0.04 Mn 0.01 Ti 0.01 Zr 0.01 W 0.01 )O2, which is different from Example 1 in that:

[0086] Step (1) Weigh 2000.0 g of Ni 0.95 Co 0.04 Mn 0.01 (OH)2 high-nickel ternary precursor, 17.3g of TiO2, 26.8g of ZrO2, 51.1g of WO3 and 981.0g of LiOH were fully mixed in a ball mill to obtain a mixture.

[0087] Step (2) The mixture is placed in an oxygen environment and calcined at 560° C. for 2 h, then heated to 760° C. at a rate of 10° C. / min and calcined for 11 h, cooled to room temperature, and sieved to obtain product 1.

[0088] The high nickel positive electrode material prepared in this example was subjected to an X-ray diffraction (XRD) test, and Topas refinement showed that the grain size was 96.7 nm and the lattice parameter c-axis was 14.2144.

[0089] Example 6

[0090] This embodiment provides a low entropy high nickel positive electrode material Li (Ni 0.91 Co 0.04 Mn 0.01 Ti 0.01 Zr 0.02 Ta 0.02 )O2, which is different from Example 1 in that:

[0091] Step (1) Weigh 2000.0 g of Ni 0.95 Co 0.04 Mn 0.01(OH)2 high-nickel ternary precursor, 53.6 g of ZrO2, 97.6 g of Ta2O5 and 992.1 g of LiOH were fully mixed in a ball mill to obtain a mixture.

[0092] Step (2) The mixture is placed in an oxygen environment and calcined at 560° C. for 2 h, then heated to 800° C. at a rate of 10° C. / min and calcined for 11 h, cooled to room temperature, and sieved to obtain product 1.

[0093] The high nickel positive electrode material prepared in this example was subjected to an X-ray diffraction (XRD) test, and Topas refinement showed that the grain size was 93.4 nm and the lattice parameter c-axis was 14.2217.

[0094] Comparative Example 1

[0095] This comparative example provides a high nickel positive electrode material Li (Ni 0.95 Co 0.04 Mn 0.01 )O2, which is different from Example 1 in that:

[0096] Step (1) Weigh 2000.0 g of Ni 0.95 Co 0.04 Mn 0.01 The (OH)2 high-nickel ternary precursor and 948.7 g of LiOH were fully mixed in a ball mill to obtain a mixture.

[0097] Step (2) The mixture is placed in an oxygen environment and calcined at 560° C. for 2 h, then heated to 690° C. at a rate of 10° C. / min and calcined for 11 h, cooled to room temperature, and sieved to obtain product 1.

[0098] The high nickel positive electrode material prepared in this comparative example was subjected to X-ray diffraction (XRD) testing, and Topas refinement showed that the grain size was 109.8 nm and the lattice parameter c-axis was 14.1881.

[0099] Comparative Example 2

[0100] This comparative example provides a high nickel positive electrode material Li (Ni 0.91 Co 0.04 Mn 0.01 Ti 0.01 Zr 0.01 Nb 0.01 Ta 0.01 )O2, which is different from Example 1 in that:

[0101] Step (1) Weigh 2000.0 g of Ni 0.95 Co 0.04 Mn 0.01(OH)2 high-nickel ternary precursor 17.3g TiO2, 26.8g ZrO2, 48.8g Ta2O5, 29.4g Nb2O5 and 992.1g LiOH were fully mixed in a ball mill to obtain a mixture.

[0102] Step (2) The mixture is placed in an oxygen environment and calcined at 560° C. for 2 h, then heated to 800° C. at a rate of 10° C. / min and calcined for 11 h, cooled to room temperature, and sieved to obtain product 1.

[0103] The high nickel positive electrode material prepared in this comparative example was subjected to X-ray diffraction (XRD) testing, and Topas refinement showed that the grain size was 101.2 nm and the lattice parameter c-axis was 14.2109.

[0104] Comparative Example 3

[0105] This comparative example provides a high nickel positive electrode material Li (Ni 0.90 Co 0.04 Mn 0.01 Ti 0.02 Zr 0.02 Nb 0.01 )O2, which is different from Example 1 in that:

[0106] Step (1) Weigh 2000.0 g of Ni 0.95 Co 0.04 Mn 0.01 (OH)2 high-nickel ternary precursor, 34.6 g of TiO2, 53.6 g of ZrO2, 29.4 g of Nb2O5 and 1000.8 g of LiOH were fully mixed in a ball mill to obtain a mixture.

[0107] Step (2) The mixture is placed in an oxygen environment and calcined at 560° C. for 2 h, then heated to 810° C. at a rate of 10° C. / min and calcined for 11 h, cooled to room temperature, and sieved to obtain product 1.

[0108] The high nickel positive electrode material prepared in this example was subjected to an X-ray diffraction (XRD) test, and Topas refinement showed that the grain size was 96.6 nm and the lattice parameter c-axis was 14.2010.

[0109] Test Example 1: Crystal morphology test

[0110] The high nickel positive electrode materials prepared in Comparative Example 1 and Examples 1 to 3 were subjected to cross-sectional scanning electron microscopy (CP-SEM) testing. The configuration entropy was modified by doping with transition metal elements, and the temperature was controlled to make the grain sizes of each example and comparative example close to each other. The degree of refinement of the primary grains was compared. Figure 2As shown in the figure, it is found that the configuration entropy of the high nickel cathode material is improved while the grains are refined, the non-directional primary grains are optimized to form a radial arrangement, the grain density is improved while the defects of the material are reduced, thereby shortening the Li + The diffusion path of Li + transmission and improve the electrical properties of materials.

[0111] Test Example 2 Cross-section - Scanning Electron Microscope Energy Spectroscopy Test

[0112] Comparative Example 2 and Example 5 were subjected to cross-sectional scanning electron microscope energy spectrum (CP-SEM-EDS) testing to analyze the distribution of Ni, Co, Mn, O, Ti, Nb, Zr, W, and Ta in the secondary particles.

[0113] Figure 3 Shown are the test results of the samples of Example 5, as Figure 3 As shown, Ni, Co, Mn, O, Ti, Nb, and W elements are evenly distributed in the particles without obvious segregation.

[0114] Figure 4 Shown are the test results of the samples of Comparative Example 2, such as Figure 4 As shown in the figure, there is uneven doping of Zr and Ta elements, and the segregation of Ta element is more serious. This is mainly because Zr 4+ The ionic radius is larger than Ni 2+ , which results in some elements being unable to enter the crystal lattice and replace transition metal sites during the calcination process; and Ta 5+ The Ta-O bond energy is too high, so the energy required to break the Ta-O bond in Ta2O5 is high, which leads to Ta segregation and reduces the kinetic properties of the material.

[0115] Test Example 3: Lithium-rich Oxide Test

[0116] Through XRD analysis of Examples 4-6 and Comparative Example 1, it was found that Nb, W, and Ta were related to Li + , O 2 - The reaction forms an ion conductive layer, and XRD detection shows the characteristic peaks of lithium-rich oxides such as Li3NbO4, Li6WO6, and Li3TaO4. Figures 5 to 7 The XRD comparison diagrams of Examples 4-6 and Comparative Example 1 are shown respectively. The free Li + , O 2 - At the same time, it does not affect the main body of the material, and increases the interface layer Li during charging and discharging. + Diffusion rate.

[0117] Test Example 4 Electrochemical Performance and Safety Performance Test

[0118] The high-nickel positive electrode oxide prepared in Examples 1 to 6 and Comparative Examples 1 to 3 was slurried with the conductive agent acetylene black and the binder PVDF in a mass ratio of 96.5:1.5:2, and the rolled positive electrode sheets were coated. The button cells were assembled in an argon atmosphere glove box, and the charge and discharge capacity and 50 cycles of button cell tests were carried out in a constant current charge and discharge mode within a voltage range of 3.0-4.3V. The test results are shown in Table 1 below; and the TG-DSC test was carried out at a voltage of 3.0-4.5V and within a range of room temperature-600°C. The test results are shown in Table 2 below.

[0119] Table 1

[0120]

[0121] Table 2

[0122]

[0123]

[0124] It can be seen from Table 1 and Table 2 that the configuration entropy modification ΔS of the high nickel positive electrode materials of Examples 1 to 3 compared with Comparative Example 1 is config <0.15R, the 3.0-4.3V are all improved, among which the electrical performance optimization of Example 2 is the most obvious, with a capacity increase of about 2.5mAh / g, and in the TG-DSC test at high voltage, Examples 1 to 3 have a stronger exothermic peak temperature and a better oxygen release rate. Compared with the configuration entropy modification of the high nickel positive electrode material of Example 1, Examples 4 to 6 have a 0.15R<ΔS config When R<0.20, due to the decrease of nickel content, the influence of Ni content on the energy density of the material exceeds that of other metal elements on the construction of electrical properties, so that the charge and discharge performance decreases, but due to the configuration entropy modification value range ΔS config <0.20R, the kinetic and thermodynamic properties of the material are also better than those of comparative examples 2 to 3.

[0125] Test Example 5 Cyclic Performance Test

[0126] The batteries prepared in Example 2 and Comparative Example 1 were disassembled before and after 50 cycles, and tested by cross-sectional scanning electron microscopy (CP-SEM). Figure 8 The CP-SEM morphology of Comparative Example 1 before and after the cycle is shown. The grains of Comparative Example 1 are in a crushed state before and after the cycle, and after the cycle, they are severely broken. Fig. 9 The CP-SEM morphology of Example 2 before and after the cycle is shown. The grain crack state of Example 2 is less, indicating that the compressive resistance of the particles is improved after the entropy value is improved, and the internal stress of the grains is reduced, which reduces the erosion of the electrolyte, so that the grain morphology after the cycle remains more intact.

[0127] At the same time, the battery was tested at 100% SOC EIS before and after 50 cycles, such as Fig.10 As shown, the interfacial impedance of Example 2 before and after cycling is lower than that of Comparative Example 1, indicating that the impedance is improved while the configuration entropy is increased.

[0128] The above description is not all embodiments. The detailed description of the embodiments of the present disclosure is not intended to limit the scope of the present disclosure for protection, but merely represents selected embodiments of the present disclosure. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present disclosure.

Claims

1. A low entropy high nickel positive electrode material, characterized in that: The low-entropy high-nickel cathode material is doped with one or more metal elements with multivalent states, and the configuration entropy modification value ΔS of the low-entropy high-nickel cathode material is config <0.2R.

2. The low-entropy high-nickel positive electrode material according to claim 1, characterized in that The chemical formula of the low entropy high nickel positive electrode material is LiNi a Co b Mn c X (1-a-b-c) O2, wherein X is a metal cation selected from Ti +4 、Ti +2 、Zr +4 、Zr +2 ,Ge +4 ,Ge +2 Sn +4 Sn +2 、 +5 、 +4 、 +3 , Nb +5 , Nb +4 , Nb +3 、As +5 、As +3 , Sb +5 , Sb +3 、V +5 、V +4 、Ru +5 、Ru +4 、Se +6 、Se +4 , W +6 , W +4 、Mo +6 and Mo +4 One or more of the following; 0.8≤a<1, 0.01≤b<0.1, 0.01≤c<0.

1.

3. The low entropy high nickel positive electrode material according to claim 2, characterized in that The configuration entropy S of the low entropy high nickel positive electrode material config satisfy: Among them, x i is the mole fraction of the cation and x j is the molar fraction of anions, N is the number of corresponding cation / anion elements; R is the universal gas constant, R = 8.314 J.mol -1 ·K -1 , S config <1R is a low entropy cathode material; configuration entropy modification value ΔS config is the difference in configuration entropy before and after doping of the positive electrode material.

4. The low entropy high nickel positive electrode material according to claim 2, characterized in that Part of the metal elements forms Li-XO lithium-rich oxide at the interface or near the surface of the low-entropy high-nickel positive electrode material; X is preferably Ti +4 、Ti +2 、Zr +4 、Zr +2 、 +5 、 +4 、 +3 , Nb +5 , Nb +4 , Nb +3 , W +6 and W +4 One or more; and / or, the low-entropy high-nickel positive electrode material is doped with no more than three metal elements.

5. The low entropy high nickel positive electrode material according to claim 1, characterized in that: The metal cation matches the lattice of the low entropy high nickel positive electrode material, and the radius of the metal cation is And / or, the grain size of the low-entropy high-nickel positive electrode material is 80 to 110 nm; and / or, the crystal parameter c-axis of the low-entropy high-nickel positive electrode material is higher than 14.

19.

6. A method for preparing a low-entropy high-nickel positive electrode material as claimed in any one of claims 1 to 5, characterized in that: include: S1, ball milling a high-nickel ternary precursor, a lithium source, and a metal source to obtain a mixture; wherein the metal element X of the metal source has multiple valence states; S2, placing the mixture in an oxygen environment, heating it to 500-600° C., calcining it for 1-6 hours, then heating it to 650-850° C., calcining it for 10-15 hours, and cooling it to room temperature to obtain a first product; S3, washing, separating and drying the first product by using a salt-free water solution to obtain a second product; S4, placing the second product in an oxygen atmosphere, heating it to 200-400° C., performing secondary calcination, and cooling it to room temperature after calcination to obtain the low-entropy high-nickel positive electrode material.

7. The preparation method according to claim 5, characterized in that: The lithium source is selected from one or more of lithium hydroxide, lithium fluoride and lithium carbonate; the metal source is selected from one or more of oxides, fluorides, carbonates, phosphates and oxalates containing element X, and the metal source is further preferably one or more of ZrO2, TiO2, Nb2O5, TaO2 and WO3.

8. The preparation method according to claim 5, characterized in that: In step S1, the molar ratio of the metal ions in the high-nickel ternary precursor and the metal source is (90-100):(10-0).

9. The preparation method according to claim 5, characterized in that: In step S2, the heating rate is 5 to 15°C / min; and / or, in step S4, the secondary calcination time is 4 to 10 hours.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the low-entropy high-nickel positive electrode material according to any one of claims 1 to 5 and / or the low-entropy high-nickel positive electrode prepared by the preparation method according to any one of claims 6 to 9.

Citation Information

Cited By

  • Preparation method of high-oxidation-state element high-entropy doped high-nickel layered positive electrode material

    CN120199811A

  • Preparation method of high oxidation state element high-entropy doped high-nickel layered positive electrode material

    CN120199811B